If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 13 = 11x Reorder the terms: 13 + 9x = 11x Solving 13 + 9x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 13 + 9x + -11x = 11x + -11x Combine like terms: 9x + -11x = -2x 13 + -2x = 11x + -11x Combine like terms: 11x + -11x = 0 13 + -2x = 0 Add '-13' to each side of the equation. 13 + -13 + -2x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 0 + -13 -2x = 0 + -13 Combine like terms: 0 + -13 = -13 -2x = -13 Divide each side by '-2'. x = 6.5 Simplifying x = 6.5
| 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m | | r^3+3r-10=0 | | 6x^2+3x-c=0 | | lg*(x-2)+lg*(x+3)=lg*14 | | (x+3i)(y-2i)=18+6i | | 11r+1=5r+19 | | 6m-12=2m+8 | | 5y-27=3y-5 | | x^2+(k-2)x+(k+3)=0 | | (7+w)(5w-2)=0 | | 2e^2x-3=4equation | | 5x^2-29x-9= | | 80=4x+2y | | -0.5x^2+36x-310=0 | | 0.5x^2+36x-310=0 | | 8-4w=2w+5 | | =3-6x-3x^2 | | 3(6x-6)=-144 | | G(x)=60-3-2x | | 4(10-x)=24 | | G(x)=60-2x | | 8(x+3)=6(x-7) | | H(x)=60+6 | | Cosz+2=0 | | 10ab-5bc=2.5 | | 7x-1=5x+10 |